Low-salinity medium for large-scale biomass production of the marine purple photosynthetic bacterium Rhodovulum sulfidophilum - Shamitha Rao Morey-Yagi; Dao Duy Hanh; Miki Suzuki; Shota Kato; Geoffrey Liou; Yuki Kuroishikawa; Ayaka Yamaguchi; Hiromasa Morishita; Masaki Odahara; Keiji Numata (PLoS ONE, 2025)
Marine purple non-sulfur bacteria such as Rhodovulum sulfidophilum are versatile due to their diverse applications in bioremediation, biotechnological production of useful materials, industrial production of value-added compounds, and agricultural fertilizers. Our previous study demonstrated the potential of its lysed and dried biomass as a nitrogen fertilizer for plant production. However, large-scale fertilizer production requires scaling up the culture to larger volumes, which is not cost-effective with currently available options for growth media. In this study, we tested a seawater-based, cost-effective alternative to the commonly used nutrient-rich culture medium for the growth of this bacterium. We found that reducing salinity from 3% to 1.2% had no adverse effects on its heterotrophic growth, dry cell yield, nitrogen content, and total amino acid composition. The nitrogen content and the weight percent of free lysine, aspartic acid, and glutamate tended to increase in the biomass obtained from cultures grown at 1.2% salinity. Under autotrophic conditions, decreasing salinity to 1.2% did not affect cell growth, final dry cell yields, and total carbon assimilation, but N assimilation remained higher. Reducing salinity to 1.2% proved to be cost-effective and feasible for the cultivation of R. sulfidophilum without increasing the risk of contamination, providing a viable alternative for its large-scale cultivation and application as a plant nitrogen fertilizer.